Effect of friendship status on primary school pupils’ attitude towards schooling and academic achievement in Oyo state, Nigeria (2017)
The importance of both attractive school and classroom contexts as social environment and optimum conditions for effective learning is acknowledged by all educators. The reason is that classroom interaction plays vital roles in the social and academic development of primary school pupils through formation of friends which is common among them. However, literature has shown that lack of positive peer interaction among primary school pupils is prevalent in Nigeria primary schools and this problem has been hindering positive peer relationship like friendship which is capable of enhancing social, attitudinal, emotional and academic development of the pupils. In fact, it has been observed that for pupils who are not acknowledged by their peers for being friendly, sociable, kind, competent, willing to help and supportive as they do to popular and friendly pupils, school can be a very unpleasant place because friendship continues to impact pupils’ attitude towards schooling and academic achievement throughout childhood. Thus, a single friendship in the classroom can be sufficient to contribute to the pupils’ overall well-being in school as well as future, lifelong development of the pupils and the society. This study therefore investigated the effect of friendship status on primary school pupils’ attitude towards schooling and academic achievement. The study design is survey research of the ex-post facto type. Five hundred and eighty seven (587) public primary school pupils randomly sampled from fourteen primary schools participated in the study. One research question was raised and answered. Four instruments were developed and validated to gather the data. Data collected were analyzed using Analysis of Variance (ANOVA). The results showed significant difference in the attitude of pupils towards schooling. The researcher concluded that friendship status is an essential determinant of pupils’ attitude towards schooling and recommendations were made that could promote pupils’ attitude towards schooling and academic achievement and by extension societal development.